Understanding learners' sense making of movement learning in physical education. Issue 2 (4th May 2019) - Rönnqvist, M.; Larsson, H.; Nyberg, G.; Barker, D.
ABSTRACT: There is a substantial body of physical education scholarship focusing on movement learning. The question of how pupils themselves make sense of movement learning has however, largely escaped attention. Answers to such a question would seem to be highly germane if educators are to engage in pupil-centered pedagogies. In light of this absence, the aim of this investigation was to describe how movement learners made sense of their own movement development. Drawing on theoretical tenets of Gilbert Ryle (2009. The concept of mind . New York, NY: Routledge) and Michael Polanyi (1969. Knowing and being. Essays by Michael Polanyi . Chicago, IL: University of Chicago Press), three cases from an investigation in which movement learning was occurring are presented. The investigation was conducted during a physical education project week with pupils from an upper secondary school. Data were produced using observations, informal interviews, semi-structured interviews, and research diaries as a group of pupils learned to juggle. The results suggest that: the aspects of moving to which learners attend change as they learn; learners have a relatively limited capacity to verbally articulate what they learn, and; learners' expectations of ideal ways of moving have considerable impact on how they come to make sense of their own ways of moving. The practical implications of these points are discussed in the final section of the paper.